2022
DOI: 10.5115/acb.21.169
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the effect of conditioned medium from endometrial stem cells on endometriosis-derived endometrial stem cells

Abstract: Endometriosis is a common, benign gynecological disease which is determined as an overspreading of endometrial tissue in exterior region of the uterine cavity. Evidence suggests that retrograde menstrual blood which contains mesenchymal stem cells with differential gene expression compared to healthy women may play a role in endometriosis creation. We aimed to identify whether the conditioned medium (CM) from menstrual blood-derived mesenchymal stem cells (MenSCs) of healthy women can affect the expression lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…In contrast, Sahraei et al found that CD9 and CD29 expression was significantly lower in E-MenSC, while CD10 was highly expressed. Moreover, after treatment with NE-MenSC-derived conditioned medium, CD10 expression decreased significantly in E-MenSCs, providing the CD10 surface marker with an important role in the diagnosis of endometriosis [16,20]. E-MenSC have been shown to possess higher proliferation and invasion capacities when compared with NE-MenSC.…”
Section: Mensc From Patients With Endometriosis (E-mensc) Display Dif...mentioning
confidence: 98%
“…In contrast, Sahraei et al found that CD9 and CD29 expression was significantly lower in E-MenSC, while CD10 was highly expressed. Moreover, after treatment with NE-MenSC-derived conditioned medium, CD10 expression decreased significantly in E-MenSCs, providing the CD10 surface marker with an important role in the diagnosis of endometriosis [16,20]. E-MenSC have been shown to possess higher proliferation and invasion capacities when compared with NE-MenSC.…”
Section: Mensc From Patients With Endometriosis (E-mensc) Display Dif...mentioning
confidence: 98%